Formation Of Independent Information Search Skills Based On Heuristic Learning Technologies - Iqbol Valiyevna Qaynarova (Euro Asian Journal Publishing, 2024)
Today, this article describes the content of forming the skills of critical thinking and independent search of information, development of educational activity and intellectual creativity of primary school students on the basis of heuristic educational technologies
Keywords: Heuristic function; creative activity; flexibility of thinking; heuristic education